A study of rhetoric based on the views of Safi Al-Din Al-Hali - Al-Shimari, Ali Mahmood Habib; Pour, Mojtaba Emrani; Gholamali, Mehran (Al-Adab Journal, 2022)
Arabic rhetoric is divided into three parts: meanings, expression and novelty. In each of them, the strategies of presenting the speech according to the needs of the listener, the method of presenting the speech and how the arrangement of the speech are stated, respectively. Great scholars have given speeches and theories in this regard. In this research, we intend to discuss his views and theories about Safi al-Din Halli, one of the scholars of rhetoric, through descriptive-analytical method by exploring the verses of Divan. Therefore, we will first introduce each of the rhetorical topics that this great scholar has referred to in his educational verses and then we explain Safiyya al-Din’s views on it and make it clear that the purpose of this precious world in these verses is to provide opinions on each of the topics of Arabic rhetoric and education to the listener. Finally, we compare the views of other scholars of this science with him in each of the issues he has raised, who have usually offered concurrent theories, but it seems that Safiyuddin’s scope of view in some cases, including the characteristics of the speaker, is wider. It is another rhetoric.